Pembelajaran Kosakata Bahasa Inggris Menggunakan Wordwall - Tiurmaya Agustina; Fauziah Nur; Fitriany Fitriany; Rita Napitupulu (Joong-Ki : Jurnal Pengabdian Masyarakat, 2022)
The purpose of this community service activity is to assist students in learning English by using Wordwall in classroom learning and to produce new English vocabulary for students. Considering that the mastery of English for students today has become something that is highly expected. However, based on existing developments, students often find difficulties in the learning process. One method that can overcome this is the Wordwall Method. This activity is carried out at one of the tutoring places for young learners, namely Tunas Education Centre for elementary school children, which is located at Jalan Sosial NO.1A. district. Tanjung Morawa. Deli Serdang, North Sumatra. The target participants are grade IV elementary school students, totaling 15 participants. The method used is the method of theory and practice. The results obtained through this training are innovative learning knowledge using Wordwall which is expected to increase students' knowledge and vocabulary. This training received a good response and with positive results as well. However, the same activities can be carried out simultaneously to get better results